Modelling energy utilization in poultry - Sakomura, N. K. [UNESP]; Fernandes, J. B.K. [UNESP]; Resende, K. T. [UNESP]; Rabello, C. B.V. [UNESP]; Longo, F. [UNESP]; Neme, R. [UNESP] (Brill Academic Publishers, 2023)
Models of daily energy requirement can help to establish better and more profitable feeding programs for poultry. Studies have been conducted at UNESP-Jaboticabal-Brazil with the aim of studying energy utilization in broiler breeders, laying hens, and broilers, and to establish metabolisable energy requirement models. The factorial approach was used to partition the energy requirements into maintenance, growth, and production components. The resulting models consider body weight, weight gain, egg production, and environmental temperature for the determination of the energy requirements of poultry. These models were evaluated in performance trials and provided good estimates. Therefore, they can be used to establish nutritional programs. The aim of this chapter is to describe the development of these models and to outline the results of our studies at UNESP.
Keywords: Energy metabolism; Energy requirement; Factorial approach; Poultry